Technology-Enhanced Learning
XXVI, 324 p.
Keywords: Technology-enhanced learning is a timely topic, the importance of which is recognized by educational researchers, practitioners, software designers, and policy makers. This volume presents and discusses current trends and issues in technology-enhanced learning from a European research and development perspective. This multifaceted and multidisciplinary topic is considered from four different viewpoints, each of which constitutes a separate section in the book. The sections include general as well as domain-specific principles of learning that have been found to play a significant role in technology-enhanced environments, ways to shape the environment to optimize learners’ interactions and learning, and specific technologies used by the environment to empower learners. An additional section discusses the work presented in the preceding sections from a computer science perspective and an implementation perspective. This book comes out of the work in Kaleidoscope: a European Network of Excellence in which over 1,000 people from more than 90 institutes across Europe participate. Kaleidoscope brings together researchers from diverse disciplines and cultures, through their collaboration and sharing of scientific outcomes, they are helping move the field of technology-enhanced learning forward.